Examination of heavy metal input from flood sediments in agricultural landscapes - Ilinskiy Andrey; Evsenkin Konstantin; Pavlov Artyom (E3S Web of Conferences)
The purpose of research is the ecological assessment of the impact of flood sedimentation on arable land of the Oka River floodplain agrolandscape. Research on studying the arrival of pollutants in the flood sediments on arable land floodplain agrolandscape was conducted in 2022-2023 on a stationary observation site of 16 ha, located 2 km from the northeastern administrative boundary of Ryazan Ryazan region (left bank of the central part of the Oka River floodplain near the village of Shumash). Studying sediment load was carried out by sampling sediments with the help of pile plastic mats imitating the top soil cover (mat area 0.14 m2) installed in advance in the control points (before the beginning of spring flooding). During the experiment, the value of sediment load was established, the content of pollutants in flood sediments in comparison with the underlying soil was studied, the degree of contamination of sediments with heavy metals and arsenic was assessed, and the structure of the influx of the studied chemical elements into the agrolandscape with flood sediments was analyzed. Of the pollutants considered, cadmium is more actively concentrated in flood sediments of the stationary observation site, followed by mercury, zinc, nickel, arsenic, manganese, lead, and copper and chromium less actively. The input of gross forms of heavy metals amounted to: copper - 260.5 g/ha; zinc - 1468.0 g/ha, lead - 255.8 g/ha; cadmium - 108.1 g/ha; nickel - 499.2 g/ha; chromium - 508.6 g/kg; mercury - 0.6 g/ha; arsenic - 115.6 g/ha; manganese - 8907.6 g/ha. The arrival of pollutants in the process of sedimentogenesis on the territory of agrolandscape in the floodplain of the Oka River indicates the need to organize and conduct environmental monitoring of the content of heavy metals and arsenic in flood sediments and underlying soil, as well as preventive measures to improve its buffer properties.